Challenges to joint planning, monitoring, and evaluation for nutrition-sensitive agriculture in Ethiopia: an exploratory qualitative study - Bezabih, A.M.; Kahsay, Z.H.; Kahsay, A.; Bekele, A.; Seid, O.; Asfaw, S.; Gebrearegay, F.; Tadesse, K.; Bazzano, A.N.; Jogo, W.; Covic, Namukolo M.; Busse, H. (Springer, 2023)
Background Nutrition-sensitive agriculture is an effective multi-sectoral approach to address the underlying causes of malnutrition. However, successful implementation requires the involvement of different sectors to jointly plan, monitor, and evaluate key activities, which is often challenged by contextual barriers. Previous studies in Ethiopia have not adequately explored these contextual barriers. Hence, the current study aimed to qualitatively explore the challenges to joint planning, monitoring, and evaluation for nutrition-sensitive agriculture among sectors in Ethiopia.